HCOOH disproportionation to MeOH promoted by molybdenum PNP complexes. Issue 39 (15th September 2021) - Alberico, Elisabetta; Leischner, Thomas; Junge, Henrik; Kammer, Anja; Sang, Rui; Seifert, Jenny; Baumann, Wolfgang; Spannenberg, Anke; Junge, Kathrin; Beller, Matthias
Abstract : Mo(0) complexes with aliphatic PNP-pincer ligands enable the first example of non-noble metal catalyzed formic acid disproportionation leading to methanol with a selectivity of up to 37% and a turnover number up to 69. Abstract : Molybdenum(0) complexes with aliphatic aminophosphine pincer ligands have been prepared which are competent for the disproportionation of formic acid, thus representing the first example so far reported of non-noble metal species to catalytically promote such transformation. In general, formic acid disproportionation allows for an alternative access to methyl formate and methanol from renewable resources. MeOH selectivity up to 30% with a TON of 57 could be achieved while operating at atmospheric pressure. Selectivity (37%) and catalyst performance (TON = 69) could be further enhanced when the reaction was performed under hydrogen pressure (60 bars). A plausible mechanism based on experimental evidence is proposed.